Strategi Pengelolaan Siaran Radio di Era Perkembangan Teknologi Internet - Kustiawan, Winda; Ramadhani, Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The advancement of communication technology demands that radio broadcast management have a strategy that can overcome tight competition in the computer era. The presence of radio broadcasts through online internet-based platforms is meant to stimulate conventional radio broadcasts to meet the needs of its listeners. Radio broadcast strategies follow technological trends through research to meet listener needs as the basis for broadcast format planning, program scheduling based on segments, and timely delivery to meet listener needs. Online radio broadcasts create new broadcast programs with the aim of expanding the global reach of listeners as a consequence of radio broadcasts in the era of technology. The ability of online radio broadcasting to explore the entire universe globally means that radio broadcast management is still sought after by listeners if it can overcome technological determinism. This radio broadcast management strategy will continue to evolve in line with technological advancements. No matter how much communication technology advances, if a radio broadcast is managed well, it will never be abandoned by its listeners.